Acute Toxicity of Aeollanthus pubescens Essential Oil with High Antimicrobial Potential against Multidrug Resistant Bacteria Isolated in Poultry Farms in Benin - Philippe Sessou*; Mahudro Yovo; Rodrigue Towanou; Yannick Ayihou; Gwladys S. Komagbe; Justin Adinci; Bruno Ayaovi Yaovi; Oscar Nestor Aguidissou; Maximin Senou; Guy Alain Alitonou; Félicien Avlessi; Souaïbou Farougou; et al. (Iranian Society of Pharmacognosy, 2019)
Background and objectives: The present work aimed to evaluate the acute toxicity of Aeollanthus pubescens essential oil, whose antimicrobial activity has been proven in vitro by previous studies and to examine the effects of this essential oil on the biochemical parameters (transaminases ALT and AST, urea, creatinine and cholesterol) and hematological and histological factors in Wistar rats subjected to this volatile oil. Methods: Nine male Wistar rats, 12 weeks old weighing more than 140 g were divided into three groups of three rats each; group one normal control rats; group two normal rats which received the extract of A. pubescens by gavage at a dosage of 2000 mg/kg of body weight and finally gropup three consisting of normal rats receiving the extract of A. pubescens by intramuscular injection at a dosage of 2000mg/kg body weight. The duration of the experiment was 14 days. Results: At the end of the study, the essential oil of A. pubescens did not cause any mortality in the experimental rats, which indicated that the extract did not exhibit acute toxicity at this dose. Biochemical and hematological analyses revealed no adverse effects (p>0.05) on the hepatic, renal, lipid and hematological parameters measured in these animals. Histological examination showed no alteration of the hepatic and renal structures. Conclusion: This oil can be considered generally recognized as safe at the experimental dosage and can be used in the fight against pathologies of bacterial origin.